2021
DOI: 10.23919/jsee.2021.000126
|View full text |Cite
|
Sign up to set email alerts
|

A learning-based flexible autonomous motion control method for UAV in dynamic unknown environments

Abstract: This paper presents a deep reinforcement learning (DRL)-based motion control method to provide unmanned aerial vehicles (UAVs) with additional flexibility while flying across dynamic unknown environments autonomously. This method is applicable in both military and civilian fields such as penetration and rescue. The autonomous motion control problem is addressed through motion planning, action interpretation, trajectory tracking, and vehicle movement within the DRL framework. Novel DRL algorithms are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…(2) Based on the reinforcement learning network. For example, Yuxie Luo [12] established an intelligent UAV model using the reinforcement learning network and built a reward function using the cooperative parameters of multiple UAVs to guide UAVs to conduct collaborative penetration; Yue Li [13] used reinforcement learning algorithms for training in four scenarios, frontal attack, escape, pursuit, and energy storage, thereby improving the intelligent decision-making level of air confrontation; Kaifang Wan [14] proposed a motion control method based on deep reinforcement learning (DRL), which provides additional flexibility for UAV penetration within the DRL framework; Liang Li [15] mainly focused on the winning region of three players in the reconnaissance penetration game, proposed an explicit policy method for analyzing and constructing barriers, and provided a complete solution by integrating the games of kind and degree.…”
Section: Related Workmentioning
confidence: 99%
“…(2) Based on the reinforcement learning network. For example, Yuxie Luo [12] established an intelligent UAV model using the reinforcement learning network and built a reward function using the cooperative parameters of multiple UAVs to guide UAVs to conduct collaborative penetration; Yue Li [13] used reinforcement learning algorithms for training in four scenarios, frontal attack, escape, pursuit, and energy storage, thereby improving the intelligent decision-making level of air confrontation; Kaifang Wan [14] proposed a motion control method based on deep reinforcement learning (DRL), which provides additional flexibility for UAV penetration within the DRL framework; Liang Li [15] mainly focused on the winning region of three players in the reconnaissance penetration game, proposed an explicit policy method for analyzing and constructing barriers, and provided a complete solution by integrating the games of kind and degree.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, some people used UAVs to carry out delivery of relief supplies, extinguishing, and so on [3][4][5]. Consequently, it has become one of the key issues for engineering applications to improve the autonomous flight capability of UAV [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The model was evaluated through a series of simulations, which showed that the developed strategy was efficient in avoiding collisions with obstacles in complex dynamic environments and narrow spaces. Wan et al [11] presented a deep reinforcement learning (DRL)-based method for motion control of unmanned aerial vehicles (UAVs) while flying autonomously through unknown dynamic environments providing good adaptability and navigation through them. Wang et al [12] proposed a globally guided reinforcement learning approach (G2RL) that incorporated a novel reward structure that generalized to arbitrary environments and that, when applied to solve the multi-robot path-planning problem, proved to be robust, scalable, and generalizable and outperformed existing distributed multi-robot path-planning methods.…”
Section: Introductionmentioning
confidence: 99%